Numerical Weather Prediction Environment for the Territory of Armenia - Khotsanyan, Tigran V. (Mathematical Problems of Computer Science, 2021)
This article is devoted to the creation and development of a numerical weather prediction environment for the territory of Armenia. One of the main features of this environment is an easy and clear web interface supporting to make numerical weather forecasts and analyze the results.